Investigation on the physical properties of clay and engineering bricks / Abdul Halim Mahfodz - Mahfodz, Abdul Halim (Faculty of Civil Engineering, 1997)
In developing country like Malaysia , the usage of bricks is very significant and wide range as construction material , commercial , recreational industrial .Bricks are local material which varies in properties from country, to country .Bricks that are properly designed and constructed are one of our most durable materials that have never been in doubt. The objectives of carrying out this study are to determine the compressive strength , flexural strength , the absorptability and permeability of bricks . The investigation on the strength behaviour of various types of locally produced bricks will be conducted . From the strength of bricks units , we can predict the strength of structural brickwork for use as load bearing wall.